Listening across borders : musicology in the global classroom - Davis, James A. (James Andrew), 1962-; Lynch, Christopher, 1984- (New York, NY : Routledge, Taylor, & Francis Group, 2022)
"Listening Across Borders: Musicology in the Global Classroom provides readers with concrete examples of how a global approach to music history can be integrated into modern curriculum, within the framework of the roots, challenges, and benefits of internationalization. In twelve essays, senior scholars with years of experience as well as younger scholars with fresh and exciting new ideas were consulted from all corners of the globe to reflect on their unique experiences. They suggest approaches and strategies that are applicable in a variety of teaching situations, with the aim of promoting internationalized teaching approaches to teachers all over the world"--
Introduction. Why Internationalization? / Christopher Lynch -- PART I. Creating Global Citizens. Western Music History as a Teaching Topic in Taiwan: Pedagogy as Transculturation / Jen-Yen Chen ; Listening Didactics as a Tool for Inclusion / Giuseppina La Face ; Using North Indian Vocal Exercises for Aural Training in the Globalized Classroom / Andrew Alter -- PART II. Teaching with Case Studies of Intercultural Encounters. Teaching Global Music History : Comparative Approaches in Chinese Historiography / Annie Yen-Ling Liu and Blake Stevens ; Listening to Intercultural Encounters in Canadian Music / Mary I. Ingraham ; Learning from Bartók : The Promises and Perils of a Globalized Music History / W. Anthone Sheppard -- PART III. Challenges and Opportunities. Global Music History in the Transnational Classroom : A View from South India / Philip Taylor ; Teaching and Learning Music History in Brazil : History, Challenges, and Proposals / Pablo Sotuyo Blanco ; Teaching Western Music in Jordan : An Anglicized-Russian Female Music Educator Perspective / Anna E. Galakhova ; Misalignment of University-Based Music Education with Modern-Day South African Musical Praxis / Madimabe Geoff Mapaya.
Keywords: Music -- Instruction and study; Multicultural education; Transnational education; Music and globalization; Education and globalization; MUSIC / General